Application of a tool for the evaluation of public and patient involvement in research. Issue 3 (13th March 2015) - Stocks, Susan Jill; Giles, Sally J; Cheraghi-Sohi, Sudeh; Campbell, Stephen M
Abstract : Objectives: Public and patient involvement (PPI) is required at all stages of research by many funding bodies such as the National Institute for Health Research (NIHR). Given the high priority of PPI within NIHR programmes and the associated costs, it is important that the process of involvement and impact of PPI on health services research is evaluated. We aimed to develop a tool to quantitatively evaluate the quality of PPI in research from a PPI participant's perspective in order to inform the researchers about absolute level of quality (cross-sectional aspect) and changes in quality over time (longitudinal aspect). Setting: A primary care patient safety translational research centre. Participants: The 12 members of the Research User Group (RUG) of Greater Manchester Primary Care Patient Safety Translational Research Centre. Interventions: By their own choice each RUG member supported a specific research theme. The level of involvement varied from commenting on documents through to designing their own research projects. Primary and secondary outcome measures planned: Measure absolute score and change in score over time in a nine-point Likert score within individuals. Compare Likert scores before undertaking PPI with scores after PPI activities. Evaluate the usefulness of a questionnaire based on a theoretical framework of personal and research factors. Results: The questionnaire had an acceptable to good level of internal consistency (Cronbach's α 0.74–0.81). The majority of the individuals met their initial expectations (11/12) and scored high across all factors. There was no significant change over time in the aggregate score over all factors and all individuals, but there were differences within individuals and factors. A ceiling effect limited the questionnaire's usefulness to measure increasing scores. Conclusions: The questionnaire has been useful in evaluating the early stages of a PPI group and may be generalisable to another setting.